Wstęp: z optymizmem w przyszłość, wierni tradycji - Pawleta, Michał; Sobkowiak-Tabaka, Iwona; Suchowska-Ducke, Paulina (Folia Praehistorica Posnaniensia, 2025)
This article offers an introduction to the 30th anniversary volume of Folia Praehistorica Posnaniensia, a peer-reviewed journal with a longstanding presence in the archaeological community. For decades, Folia has been an important forum for exchanging scientific ideas in archaeology. The journal presents research on the prehistory and early Middle Ages of Central Europe, Mediterranean archaeology, and, in recent years, interdisciplinary areas and contemporary archaeology. This volume is being published at a time of symbolic significance, given the journal’s 30th anniversary and the changes in the editorial team. The new editors continue the journal’s mission by combining respect for tradition with an openness to new research, theoretical, and methodological perspectives. They emphasize the importance of pluralism in contemporary archaeology, which promotes the discipline’s intellectual dynamism and development rather than weakening it. The volume’s content reflects this diversity. Eleven articles address issues ranging from the Neolithic period to the 21st century and cover topics such as field studies, interdisciplinary analyses, and reflections on cultural heritage and archaeological theory. Both established scientists and younger researchers are given a voice. Folia Praehistorica Posnaniensia remains a space for creative dialogue and the exchange of experiences. In keeping with the principles of scientific integrity, interdisciplinarity, and openness, the editors invite contributions to the journal that consider the future of archaeology as a dynamic, socially engaged discipline sensitive to the changing world.